PENGARUH GAYA MENGAJAR GUIDED DISCOVERY TERHADAP HASIL BELAJAR PASSING SEPAK BOLA SISWA KELAS VIII SMP NEGERI 9 BINJAI - Fahri Ridwan; Suharjo; Raswin; Ade Ros Riza; Iwan Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Guided Discovery teaching style on the learning outcomes of football passing skills among Grade VIII students of SMP Negeri 9 Binjai. This research was conducted at SMP Negeri 9 Binjai from April 6, 2026 to April 30, 2026, with the population consisting of all eighth grade students. The sample of this study included class VIII-5 as the control group and class VIII-6 as the experimental group, selected using the cluster random sampling technique. This study employed a quantitative approach with an experimental method, using a Quasi Experimental Design which involved pre-test, treatment, and post-test. The research instrument used was a football passing practice test, while data collection techniques included interviews, tests, and documentation. The data analysis techniques used were normality test, homogeneity test, and hypothesis testing (t-test). The results of the normality test showed that the pretest score of the experimental class was 0.138 and the post-test score was 0.060. Meanwhile, the control class obtained a pre-test score of 0.200 and a post-test score of 0.055. All data were normally distributed as the significance values were greater than 0.05. The homogeneity test result showed a value of 0.052 > 0.05, indicating that the data were homogeneous. Furthermore, the results of the hypothesis test (t-test) showed that the t-value was 5.291 and the t-table value was 2.001, which means that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that there is an effect of the implementation of the Guided Discovery teaching style on the learning outcomes of football passing techniques in eighth grade students of SMP Negeri 9 Binjai.